Desenvolvimento de um novo modelo para o estudo do acidente vascular cerebral perinatal - Mendes, Tânia Vanessa Faustino (2018)
Perinatal stroke is a pathologic condition that occurs between the 20th week of gestation and the 28th day after birth. Despite its incidence being comparable to stroke in adults and being one of the most common causes of hemiplegic cerebral palsy, among other incapacitating symptoms, perinatal stroke remains a poorly studied subject. The evident pathophysiology underlying perinatal stroke is still not well understood, although inflammation and prothrombotic mechanisms seem to have a prevalent role. In this way, the aim of this study was to establish a valid model to study perinatal stroke that would more closely relate to the human pathophysiology. We used oorganotypic hippocampal slice cultures from 2-3-day old mice and then quantified the expression of ionised calcium binding adaptor molecule 1 (a microglia marker), arginase-1 (a M2 microglia marker) and vascular endothelial growth factor receptor, after oxygen and glucose deprivation. The induction of oxygen and glucose deprivation mimics ischaemic conditions. All three molecules were increased after this deprivation, comparing to control (cells not exposed to injury), suggesting that microglia proliferate and adopt a protective phenotype in response to injury. In summary, inflammation seems to be an underlying mechanism in perinatal stroke, as well as microglia seems to be an important mediator. Further investigation is needed in this area in order to better understand the pathophysiology of perinatal stroke and to improve the development of new therapies.